2001
DOI: 10.1063/1.1420434
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and properties of ferromagnetic co-doped TiO2 anatase

Abstract: We have used oxygen-plasma-assisted molecular-beam epitaxy (OPA-MBE) to grow CoxTi1−xO2 anatase on SrTiO3(001) for x=∼0.01–0.10, and have measured the structural, compositional, and magnetic properties of the resulting films. Whether epitaxial or polycrystalline, these CoxTi1−xO2 films are ferromagnetic semiconductors at and above room temperature. However, the magnetic and structural properties depend critically on the Co distribution, which varies widely with growth conditions. Co is substitutional in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
223
2
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(245 citation statements)
references
References 9 publications
15
223
2
3
Order By: Relevance
“…19 000 cm -1 (ε ≈ 6 M -1 cm -1 ) that can be tentatively associated with the low symmetry split 4 T 1 (F) → 4 T 1 (P) ligand-field transition of pseudo-octahedral Co 2+ . The analogous transition in Co(H 2 O) 6 2+ is observed at 19 400 cm -1 (ε = 4.8 M -1 cm -1 ), 23 and although a similar ligand field strength is anticipated for Co 2+ in anatase TiO 2 , it is expected to be substantially broadened in the latter by the reduction in site symmetry and by possible charge compensation inhomogeneities. The presence of this transition is confirmed by MCD spectroscopy ( Figure 3B), which reveals a broad negative pseudo-A term feature in the same energy region (-19 000 cm -1 , + 21 500 cm -1 ).…”
Section: Results and Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…19 000 cm -1 (ε ≈ 6 M -1 cm -1 ) that can be tentatively associated with the low symmetry split 4 T 1 (F) → 4 T 1 (P) ligand-field transition of pseudo-octahedral Co 2+ . The analogous transition in Co(H 2 O) 6 2+ is observed at 19 400 cm -1 (ε = 4.8 M -1 cm -1 ), 23 and although a similar ligand field strength is anticipated for Co 2+ in anatase TiO 2 , it is expected to be substantially broadened in the latter by the reduction in site symmetry and by possible charge compensation inhomogeneities. The presence of this transition is confirmed by MCD spectroscopy ( Figure 3B), which reveals a broad negative pseudo-A term feature in the same energy region (-19 000 cm -1 , + 21 500 cm -1 ).…”
Section: Results and Analysismentioning
confidence: 76%
“…6 The origin of this ferromagnetism continues to be debated in the literature, however. Some thin films have been shown to contain cobalt metal nanoparticles, 7,8 fostering the widespread belief that metallic nanoparticles are responsible for the ferromagnetism in other samples as well.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the location of Co dopants in this material (substitutional versus interstitial), their oxidation state, and their magnetic properties have been the subject of intense scrutiny. 2,3,4,6,8 Furthermore, it has been suggested that O vacancies, which are believed to give rise to the observed n-type behavior in pure TiO 2 anatase, 10 may provide free electrons which mediate the exchange interaction between the Co dopants. 3,4 This possibility is very different from the hole mediated exchange interactions which are believed to describe ferromagnetic order in a wide variety of other dilute magnetic semiconductors, including InMnAs, GaMnAs, and MnGe, 11,12,13 and may have a direct bearing on the origin of the anomalously high Curie temperature observed in Co-doped TiO 2 anatase.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,5,6,7,8,9 One promising line of inquiry is to understand first the role of dopants and native defects in the TiO 2 host. For example, the location of Co dopants in this material (substitutional versus interstitial), their oxidation state, and their magnetic properties have been the subject of intense scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by theoretical predictions [1,2], much work has been done on the transition-metal doped oxides in which room-temperature ferromagnetism has been observed, including ZnO [3], TiO 2 [4,5] and SnO 2 [6][7][8]. However, compared with the booming materials research on the magnetic oxide semiconductors, the understanding of their magnetism is still in its infancy, with an ongoing debate about intrinsic ferromagnetism and extrinsic magnetic properties.…”
mentioning
confidence: 99%